ANALISIS PEMAHAMAN PENERAPAN LITERASI KEUANGAN ANAK-ANAK YANG MEMPUNYAI ORANGTUA PELAKU USAHA DAUR ULANG BARANG BEKAS - Zurfani Rachmina Putri; Yohanes Hadi Soesilo (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
The purpose of this study is to analyze the understanding the application of financial literacy children who have parents of recycled business actors. The results of the study show that parents have an important role in teaching children about financial management early on. Understanding of the application of financial literacy can be seen from indicators of budgeting, loans, savings and investment. Classification of understanding of the application of child financial literacy is divided into three, namely, sufficient literate, less literate, and not literate.